Easy and Complicated" Feature in the Tales of Sa’di'sGolestan; a Morphological Explanation - Sare Zirak; Hadis Azizian Gilan (مطالعات زبانی و بلاغی)
Most criticisms have justified the stylistic feature of the "easy and complicated" in the Golestan (a Persian literary book written in prose by Saa’di) through classic rhetoric, but new approaches to literary criticism justify it from a structural point of view. Present paper, use morphological analysis for explaining the "easy and complicated" feature of the book from a structural point of view. As results show, the tales in Golestan have a very simple structure so that they often have no more than two or three characters, but the existence of a deeper and comprehensive plan in the underline of the entire text turns the separated tales to components of a complicated building. The absence of problem-solving and its mechanisms makes simplified the structure of the tales. The manner of the distribution of the characters, functions, and initial situations, in the level beyond mere individual narratives, has provided a comprehensive coherence in the text, which explain how Saa’di create a new version of rhetoric in the way of "how to say". Combining simple and micro narrative tales with a well-structured macro text, makes the stylistic feature of the Golestan as something non-imitable.